Role of Works of Kazakh Writer Dulat Issabekov in Modern National - Sultanbekova, Zhaudir; Toty Koshenova, Kulbek Yergobek, Kalipa Atemova (Opción, 2019)
The article presents views on the essence and importance of the works of Dulat Issabekov, his potential in modern society and place in the world of literary art. The methodological basis of the research was comparing ideas and the works of Kazakh writers. As a result, literary works of Dulat Issabekov, a well-known Kazakh writer and playwright, are aimed at fostering human values and spiritual and moral qualities of a man. In conclusion, the artwork influences the soul and feelings of a person and on this basis encourages to think wisely.